PENGARUH HARGA, CITRA PERUSAHAAN, KUALITAS PELAYANAN, KEPUASAN, DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN JASA PENGIRIMAN TIKI DINOYO - David David Erdiansyah; Rois Arifin; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine the effect of the company's image price, service quality, satisfaction and trust in customer loyalty in Dinoyo TIKI delivery services, this type of research uses explanatory research with its quantitative approach, the population in this study amounted to 293 sampling techniques using slovin formula with taking techniques The sample in this study was purposive sampling, this technique was taken to obtain samples that fit the criteria.The sample in this study was 75 respondents of Dinoyo TIKI customers, using the instrument test that is the validity and reliability test, the classic assumption test is the normality test, multicollinearity test, heterokedasticity test, and the hypothesis test that is the simultaneous F test and t test, the results of this study are partially there is a positive influence of the company's image variable, service quality, satisfaction and trust towards customer loyalty, but there is a negative influence of the price variable on customer loyalty, simultaneously the price variables, company image, service quality, satisfaction and trust simultaneously influence customer loyalty.Keywords: price, image, service quality, satisfaction, trust, customer loyalty